When free markets fail : saving the market when it can't save itself - McCleskey, Scott (Hoboken, N.J. : Wiley, 2010)
"Authoritative guidance for navigating inevitable financial market regulation The reform of this country's financial regulation will be one of the most significant legislative programs in a generation. When Free Markets Fail outlines everything you need to know to stay abreast of these changes. Written by Scott McCleskey, a managing editor at Complinet, the leading provider of risk and compliance solutions for the global financial services industry. Looks at the intended result of these regulations so that institutions and individuals will have a greater understanding of the new regulatory environment. Offers a realistic look at how these regulations will affect anyone who has a bank account, a car loan, a mortgage or a credit card. Covers the reforms that have been enacted and looks forward to future reforms. Both theoretical and practical in approach, When Free Markets Fail provides a strong overview of coming regulation laws with insightful analysis into various aspects not easily understood."--
Chapter 8: Transparency: Letting the Sun Shine In, or Sipping Water from a Firehose?Chapter 9: Rebuilding the Regulatory Structure; Chapter 10: Rating the Raters: The Role of Credit Rating Agencies; Chapter 11: The Politics of Regulation; Chapter 12: Nice Law, Now Go Do It: Regulators and Compliance Officers; Chapter 13: Cost-Benefit Analysis; Chapter 14: It's a Small World, After All; Chapter 15: Where Do We Go from Here? Conclusions, Observations, and Recommendations; Ch.
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Financial institutions -- State supervision -- United States; Financial institutions -- Government policy -- United States; x; x; BUSINESS & ECONOMICS -- Banks & Banking; Financial institutions -- Government policy; Financial institutions -- State supervision; United States